1989
DOI: 10.1038/ki.1989.30
|View full text |Cite
|
Sign up to set email alerts
|

Peritonitis in peritoneal dialysis: Bacterial colonization by biofilm spread along the catheter surface

Abstract: We have used modern techniques of direct microscopic examination and quantitative bacterial recovery to show the existence of a route of bacterial colonization along the external and internal surfaces of Tenckhoff catheters implanted in experimental animals. The external route of progressive bacterial colonization extends from the cutaneous exit site through the dacron cuff and into the peritoneum. Bacterial growth along this route consists primarily of glycocalyx enclosed bacterial biofilms adherent to cathet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 17 publications
1
39
0
3
Order By: Relevance
“…Thus, the slow bactericidal effect observed with in vitro models for the study of antibiotic activity against adherent bacteria might relate more closely to the clinical situation than antibiotic exposure of suspended cultures. In fact, several histologic studies suggest that populations ofadherent organisms can be found in infected patients not only on implanted devices, but also on catheters, native heart valves, or bone structures [7,8,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the slow bactericidal effect observed with in vitro models for the study of antibiotic activity against adherent bacteria might relate more closely to the clinical situation than antibiotic exposure of suspended cultures. In fact, several histologic studies suggest that populations ofadherent organisms can be found in infected patients not only on implanted devices, but also on catheters, native heart valves, or bone structures [7,8,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…This break-in period may prevent dialysate leak and allow more rapid and uncomplicated wound healing [16]. However, even with an optimal implantation technique in a rabbit model of peritoneal dialysis, bacterial colonization proceeds via this subcutaneous route [17]. Most peritoneal catheter surfaces were covered with bacterial biofilm within 3 weeks after the implantation despite delayed beginning of bag exchanges after the implantation [17].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these studies (Table 1) demonstrate the presence of a microbial biofilm on the catheter surface, despite the absence of infection, suggesting that it is not the infectious process that gives rise to colonization, but rather that biofilms may act as a reservoir of microorganisms. Indeed, it has been hypothesized that the development of peritonitis depends on the initiation of dialysis (Read et al 1989;McDermid et al 1993) and on the ability of microorganisms to disperse from the biofilm (Verger et al 1987;Dasgupta et al 1992). However, further studies are required to elucidate the biofilm-associated infections in PD, as it was found that the microorganisms colonizing the catheter may not parallel those causing the peritonitis (Marrie et al 1983;Rodriguez-Carmona et al 2000).…”
Section: S Epidermidismentioning
confidence: 99%